Pelatihan Pembuatan Makanan Sehat Brownies Berbahan Dasar Wortel Untuk Peningkatan UMKM Desa Sindangjaya Cianjur Jawa Barat - Setiawan, Rochiyat; Melati, Dewi; Widyarto, Ervan Yudi; Kamila, Sintsa Syaila; Xania, Clarance (LPPM UMRI, 2025)
Abstract Desa Sindangjaya, which is fertile and has high potential in the agriculture and agro-tourism sectors, faces several challenges that need to be addressed to improve the local economy. One main issue is the decline in carrot production due to weather factors and external competition. Additionally, the lack of entrepreneurial knowledge and practical skills among the community hinders the development of local businesses. To overcome these problems, innovative training programs are needed to teach product diversification and business skills development. Using direct training methods, residents of Sindangjaya Village, especially farmers and youth, will be provided with knowledge on creating innovative products such as carrot brownies that are high in nutritional value and commercially attractive. This activity involves collaboration with the village government, community-owned enterprises, and higher education institutions, all working together to enhance community skills and managerial capacity. The results of this training activity show an increase in the skills and knowledge of participants in making carrot-based brownies. Participants are able to produce attractive and marketable brownie products, and understand the importance of good packaging to attract consumers. In addition, this activity has also succeeded in building networks between MSME actors . Keywords: Training, Making Healthy Food, Carrot-Based Brownies, MSMEs